Guilherme Zarvos and CEP 20.000: new politics of poetry in the city - Fernandes, Thiago (2023)
In this article, the poetic production around the poetry collective CEP 20.000 — Centro de Experimentação Poética —, created in 1990 in Rio de Janeiro, and one of its creators, the poet Guilherme Zarvos, were analyzed, with a view to the idea that the artistic, literary, and cultural scene of the 1990s seem to accompany, in Brazil, a certain political and social transformation operated in the means of production, responding to this transformation in its own way. An update of the concept of “expanded field” for poetry is proposed, no longer thinking about the term from the expansion that it describes in the means of art production, but above all from its relationship with the modes of production.